Detroit 139: Archaeology and the Future-Making of a Post- Industrial City - Ryzewski, Krysta (Journal of Contemporary Archaeology, 2019)
The future-making efforts currently unfolding in Detroit have direct implications on the extent to which the city’s pasts will be included in the narratives of generations to come. This essay evaluates current tensions between developers and preservation-oriented stakeholders. In doing so, it lays the groundwork for considering how archaeological initiatives and anthropological treatments of heritage might fit within revitalization efforts. Examples of grassroots, community-led projects undertaken by archaeologists and local partners demonstrate the potential for archaeology to contribute to the maintenance of community heritage and the shape of the city’s future.